Clinical validation of the Symptom Self-rating Scale for Schizophrenia (4S) among inpatients. (2nd August 2021) - Kølbæk, Pernille; Guinart, Daniel; Opler, Mark; Correll, Christoph U.; Mors, Ole; Østergaard, Søren D.
Abstract: Purpose: Self-reports of psychosis-related symptoms may be a valuable supplement to clinician-ratings, but more validation studies are required. The aim of this study was to conduct clinical validation for the Symptom Self-rating Scale for Schizophrenia (4S) in an inpatient setting. Materials and methods: Inpatients diagnosed with schizophrenia were invited to participate in the study. The participants completed the 4S, the 5-item World Health Organization Wellbeing Index (WHO-5) and the Sheehan Disability Scale (SDS) at two time points. Trained raters assessed participants using the 6-item Positive And Negative Syndrome Scale (PANSS-6). The relationship between the 4S and PANSS-6, self-reported side effects, functioning and wellbeing was assessed using Spearman's correlation coefficient (rho). Results: Sixty-one participants completed the 4S at least once (yielding a total of 91 completed 4S questionnaires). The 4S total score was weakly correlated with the PANSS-6 total score (rho = 0.37, p  < 0.001). The rho's for individual 4S and PANSS-6 subscales and item comparisons ranged from −0.24 (thought disorder) to 0.69 (hallucinations). Finally, the 4S hallucination subscale was also sensitive to change. The 4S was strongly inversely correlated with wellbeing (WHO-5) and moderately inversely correlated with functioning (SDS total score). Conclusion: The 4S holds promise as a valid self-report of core schizophrenia symptoms among inpatients. While the hallucination subscale seems superior to existing scales, the thought disorder subscale needs to be re-developed.